Parental involvement in monitoring foundation students’ online learning in Malaysia - Geok Shim, George Tan; Abdullah, Abdul Halim (Institute of Advanced Engineering and Science, 2025)
This study examined the parental involvement in monitoring their children online learning at foundation level through the parents’ perspectives, challenges and satisfaction. In addition, this study explored the relationship between parent’s perspectives on student’s online learning and parents’ demographic information (number of households, household income, and education level). This study employed a cross-sectional survey design, where a questionnaire was used for data collection. A total of 276 samples were selected randomly from parents who enrolled their children at a foundation center in a selected year. Data of the study were analyzed through descriptive (mean, standard deviation, percentage) and inferential statistics (Sperman’s correlation) using SPSS version 23. The findings of the study showed that majority of the parents have positive perspectives and high satisfactions towards involvement in monitoring foundation students’ online learning at home. The findings also revealed a strong positive correlation between parental perspectives towards involvement in monitoring foundation student’s online learning and household income as well as parents’ education level. The outcome of the study highlighted the parental readiness and awareness in their role in monitoring students’ online learning in tertiary education level while also providing awareness to educators on its importances and challenges in their online learning classes.